(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Objective: The aim of this study was to evaluate the early and late (6 months after surgery) complications in patients undergoing thyroid surgery. Material & methods: A retrospective study was done from January 2015 to December 2019 in the Department of ENT & Head Neck Surgery, Enam Medical College & Hospital. One hundred and sixty three patients with both benign & malignant thyroid disease underwent surgical treatment was selected for this study. Patients were followed up for six months and peroperative & postoperative complications were evaluated. Results: Out of 163 patients 132(80.9%) cases were benign and 31(19.1%) cases were malignant. Total thyroidectomy was done in 71(43.56%) patients and hemithyroidectomy was done in 82(50.3%) patients and 10(6.13%) patients had other thyroid surgery. 29(17.80%) patients develop complications after thyroid surgery. Most common post operative complication was hypoparathyroidism with a incidence of 17(10.43%). 15(9.20%) patients developed temporary hypocalcaemia and 2(1.23%) patients developed permanent hypocalcaemia. Others complications were recurrent laryngeal nerve (RLN) palsy 2(1.23%), superior laryngeal nerve (SLN) palsy 3(1.84%), wound infection 2(1.23%), haematoma 1(0.61%) and hypertrophied scar 4(2.45%). Conclusion: Hypocalcaemia was the most frequent post-thyroidectomy complication, while voice change, seroma, haematoma, wound infection and hypertrophied scar are additional complications. Surgeons have to pay attention to curtail the complications during thyroid surgery. Bangladesh J Otorhinolaryngol 2022; 28(1): 50-55